The Impact of Selected Biotechnology Processes for Sustainable Development of the Environment and Human Life - Badora, Aleksandra; Celińska, Magdalena (Problemy Ekorozwoju, 2020)
The aim of this work was to show what effect biotechnology can have on the quality of human life, and on the condition of the natural environment. A number of biotechnological processes have been analyzed that can significantly improve the quality of human life, while at the same time caring for the natural environment. The prospects for the development of these processes on the global and Polish market were also analyzed. As it turned out, some of the process analyzed need further refinement to be implemented on a global scale, while others may be successfully implemented in the coming years, contributing to the improvement of the quality of such aspects of human life high-quality food products, health protection and good public health. Biotechnological processes may also have wide application in the protection and remediation of the natural environment.